Lateral approach for insertional Achilles tendinitis with Haglund deformity - Jiantao Jiang; Cheng Wang; Shaoling Fu; Jiazheng Wang; Chenglin Wu; Guangxiao Yao; Guoxun Song; Wenqi Gu; Kai Yang; Jianfeng Xue; Zhongmin Shi (Frontiers in Surgery, 2023)
ObjectiveThe study aims to investigate the functional outcome of the lateral approach for insertional Achilles tendinitis (IAT) with Haglund deformity.MethodsFrom January 2016 to September 2019, 14 cases of IAT with Haglund deformity that resisted conservative treatment received surgery in our department. A lateral approach was used to debride the bony and soft tissue and reattach the insertion of the Achilles tendon. The Visual Analog Scale (VAS), American Orthopedic Foot and Ankle Score (AOFAS), and Victorian Institute of Sport Tendon Study Group-Achilles Tendinopathy score (VISA-A) were used to evaluate clinical outcomes.ResultThe mean patient age was 39.57 years at the time of surgery. The mean follow-up was 14.74 months. The mean VAS score significantly decreased from 4.86 ± 0.86 preoperatively to 1.21 ± 1.58 postoperatively (P < 0.001). The mean AOFAS score significantly improved from 66.64 ± 6.23 preoperatively to 90.21 ± 11.50 postoperatively (P < 0.001). The mean preoperative and the last follow-up VISA-A were 66 (range 56.75–69.25) and 86 (range 75.75–97.00) points, respectively (P < 0.05).ConclusionThe lateral approach was effective and safe for IAT with Haglund deformity. Moreover, the mid-term functional outcome was promising.Level of Clinical EvidenceIV